2010
DOI: 10.1128/jb.00161-10
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of High-Affinity Iron Acquisition Homologues in the Tsetse Fly SymbiontSodalis glossinidius

Abstract: Sodalis glossinidius is a facultative intracellular bacterium that is a secondary symbiont of the tsetse fly (Diptera: Glossinidae). Since studies with other facultative intracellular bacteria have shown that high-affinity iron acquisition genes are upregulated in vivo, we investigated the regulation of several Sodalis genes that encode putative iron acquisition systems. These genes, SG1538 (hemT) and SG1516 (sitA), are homologous to genes encoding periplasmic heme and iron/manganese transporters, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…The hemR mutant (URSOD22) was constructed using the Targetron intron mutagenesis kit (Sigma-Aldridge, St. Louis, MO) as described previously (16). Briefly, the group II intron on pACD4K-C-loxP was altered according to the manufacturer's instructions to contain a hemR-targeting site located 1,239 bp 3= of the hemR start codon.…”
Section: Construction Of Sodalis Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hemR mutant (URSOD22) was constructed using the Targetron intron mutagenesis kit (Sigma-Aldridge, St. Louis, MO) as described previously (16). Briefly, the group II intron on pACD4K-C-loxP was altered according to the manufacturer's instructions to contain a hemR-targeting site located 1,239 bp 3= of the hemR start codon.…”
Section: Construction Of Sodalis Mutantsmentioning
confidence: 99%
“…Sodalis produces several putative iron ac-quisition systems, including a previously characterized plasmidcarried (pSG1) mechanism that synthesizes and transports the iron-capturing siderophore achromobactin (15). Additionally, three Sodalis genes (hemT, hemU, and hemV) are homologous to well-characterized high-affinity ABC transport systems that transport heme through the inner membrane in other bacteria (15)(16)(17)(18)(19)(20), and Sodalis contains a putative gene (hemR) that may encode an outer membrane heme receptor. Finally, the tonB gene is present in Sodalis.…”
mentioning
confidence: 99%
“…In blood-feeding insects, iron is a component of blood meal hemoglobin and is sequestered within host storage molecules, including heme, transferrin, ferritin, and iron-containing proteins (11)(12)(13). Sodalis has several putative iron acquisition systems, including a siderophore system that synthesizes and transports the siderophore achromobactin (14,15). Siderophores are iron-chelating molecules secreted by microbes.…”
mentioning
confidence: 99%
“…Thus, expression of iron acquisition systems is repressed when sufficient iron is present in the cell (18). Although Sodalis was initially reported to lack the fur gene (17), further annotation of the genome indicated that the commensal bacterium does contain a functional fur gene whose product regulates the expression of putative heme and Sit iron acquisition systems (14).…”
mentioning
confidence: 99%
“…Whereas this process has a streamlining effect, eliminating genes that are no longer required for the symbiotic lifestyle, it also drives a reduction in metabolic plasticity, yielding fastidious bacteria that have proven to be difficult to manipulate in the laboratory due to their low growth rate, high level of susceptibility to contamination, and complex nutritional requirements (12). To date, only a few studies have utilized genetic techniques to explore the nature of host-symbiont interactions (4,5,14), and the implementation of these techniques has proved arduous and unreliable over the long term. In the current study, we report on the adaptation and optimization of the lambda Red recombineering strategy (6) for the genetic manipulation of the tsetse fly endosymbiont Sodalis glossinidius (Fig.…”
mentioning
confidence: 99%